Implementasi Pengenaan Tarif Progresif Terhadap Wajib Pajak Kendaraan Bermotor - Atapary, Febrian; Alfons, Saartje Sarah; Tita, Heillen Martha Yosephine (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Tax is a people's contribution to the State based on the law, so that it can be enforced, where the Taxpayer does not get a direct counter-achievement. The constitutional basis of the obligation to pay taxes is regulated in Article 23A, the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945. Dues from the people to the State, as a form of participation as well as contributions from citizens to the State.Purpose of Writing/Research: This study aims to determine the basis of imposition of Motor Vehicle Tax for Motor Vehicle Taxpayers and to examine and analyze the legal consequences of implementing progressive rates for Motor Vehicle Taxpayers.Purposes of the Research: This study aims to determine the basis for the imposition of Motor Vehicle Tax for Motor Vehicle Taxpayers and to examine and analyze the legal consequences of implementing progressive rates for Motor Vehicle Taxpayers.Results of the Research: The results showed evidence of payment of progressive vehicle tax. Taxpayers, progressive tax on motor vehicle tax is an individual who owns a motor vehicle. Article 6 paragraph (2) of Law Number 28 of 2009 concerning Regional Taxes and Regional Levies stipulates that a progressive tax is imposed on the ownership of private motorized vehicles, both two-wheeled and four-wheeled, based on the same name and/or address.